Amorfrutins Relieve Neuropathic Pain through the PPARγ/CCL2 Axis in CCI Rats - Pengfei Gao; Jiayu Wang; Zhen Su; Fayin Li; Xianlong Zhang (PPAR Research)
Neuropathic pain is a public health problem. Although many pharmaceuticals are used to treat neuropathic pain, effective and safe drugs do not yet exist. In this study, we tested nociceptive responses in CCI rats, and ELISA assay was performed to examine the expression of proinflammatory cytokines. We found that amorfrutins significantly reduce the pain behaviors in CCI rats and suppress the expression of proinflammatory cytokines (TNFα, IL-6, and IL-1β) and chemokines (CCL2/CCR2) in the spinal cord. However, concurrent administration of a PPARγ antagonist, GW9662, reversed the antihyperalgesic effect induced by amorfrutins. The results indicate that amorfrutins inhibit the inflammation and chemokine expression by activating PPARγ, thus relieving neuropathic pain in CCI rats. Therefore, PPARγ-CCL2/CCR2 pathway might represent a new treatment option for neuropathic pain.